PENGARUH MEDIA DAKON TERHADAP PENALARAN MATEMATIS SISWA MA AL MALIKI SUKODONO - Seravine Zalfa Audia; Ridho'i, Mohammad; Agustin, Devi Rahayu; Khasanah, Dina Ardiyanti; Maharani, Nabila Sasqia; Lestari, Putri Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to measure the impact of using dakon media on the mathematical reasoning abilities of class X students of MA Al Maliki Sukodono. In addition to testing the significance of the influence, the researcher also measured the extent of improvement in students' abilities after using this concrete manipulative media. The main problem in this study is the difficulty of students in understanding the arithmetic operations of arithmetic sequences, especially in determining the formula for the nth term and drawing logical mathematical conclusions. Methodologically, the researcher used a quantitative approach with a quasi-experimental method. The research design applied the Posttest-Pretest Non-Equivalent Control Group model. The researcher determined the sample using a purposive sampling technique consisting of two classes. Class X-A with 19 students became the control class who learned with the conventional lecture method. Class X-B with 19 students became the experimental class who learned using dakon media. The researcher collected data through mathematical reasoning essay tests and student response questionnaires which were proven to be valid and reliable. The data analysis of this research used the nonparametric Mann-Whitney test and N-Gain index analysis. The results of the data analysis showed two important findings that complement each other. The Mann-Whitney test yielded a significance value of 0.755. This value is greater than the 0.05 significance level (0.755 > 0.05), so the researchers accepted the null hypothesis (H0) and rejected the alternative hypothesis (H1). This statistical finding proves that there is no significant difference in final scores directly between the control and experimental classes. Meanwhile, the N-Gain index test showed a significant difference in learning ability growth descriptively. The control class only recorded an average N-Gain of 0.03, which is considered low. The experimental class using dakon media achieved an average N-Gain of 0.41, which is considered moderate. Questionnaire response data supported these results by showing that students became more active and understood the material on arithmetic sequences more easily through dakon visualization. The researchers concluded that learning with dakon media was far more effective in improving students' mathematical reasoning abilities than conventional lecture methods.